Assessment of seed quality of groundnut (Arachis hypogaea L.) during storage - P. A. RAUT; M. T. BHINGARDE; D. V. DESHMUKH (Seed Research, 2026)
The kernels and pods of three groundnut varieties were stored in HDPE bags under cold (5-10 °C) and ambient temperatures for a period of 270 days at Gene Bank, Medicinal and Aromatic Plant Project, M.P.K.V., Rahuri and Seed Technology Research Unit, M.P.K.V., Rahuri, respectively to assess the seed quality parameters and storability. The experiment was laid out in Factorial Completely Randomized Design (FCRD) in four replications. The study revealed that varieties, storage temperature, kernels and pods had significant effect on seed quality of groundnut during storage. Among the varieties, the variety Phule Unnati (V₁) showed greater storability than variety RHRG-6021 (V₂) and JL-501 (V₂). The seeds of var. Phule Unnati (V₁) maintained storability above Minimum Seed Certification Standards (MSCS) for 270 days, irrespective of storage temperature and kernels and pods. The seeds in the form of pods (F₂) stored at cold temperature at 5-10°C (T₁) influenced the seed quality and storability significantly. The maximum increase in storability (90 days) was observed in pods (F₂) under the cold temperature (T₁) as compared to ambient temperature (T₂) and maintained storability above MSCS for 270 days irrespective of variety. The variety Phule Unnati stored in the form of pods at cold temperature (5-10 °C) retained better seed quality up to 270 days of storage. It also exhibited higher vigour index, lower electrical conductivity and less seed mycoflora.